Analysis of SMN protein in umbilical cord blood and postnatal peripheral blood of neonates with SMA: a rationale for prompt treatment initiation to prevent SMA development - Noriko Otsuki; Tamaki Kato; Mamoru Yokomura; Mari Urano; Mari Matsuo; Emiko Kobayashi; Kazuhiro Haginoya; Hiroyuki Awano; Yasuhiro Takeshima; Toshio Saito; Kayoko Saito (Orphanet Journal of Rare Diseases)
Abstract Background Spinal muscular atrophy (SMA) is a severe genetic neuromuscular disease caused by insufficient functional survival motor neuron protein (SMN). The SMN expression level in the spinal cord is highest during the 2nd trimester of the foetal period. We previously reported the SMN spot analysis in peripheral blood using imaging flow cytometry (IFC) as a biomarker of functional SMN protein expression. In this study, we analysed neonatal cord blood, postnatal peripheral blood, and maternal peripheral blood in presymptomatic five infants whose sibling has type 1 SMA to estimate prenatal and postnatal SMN dynamics before the onset of severe SMA. Results Data from 37 untreated patients with SMA showed that SMN-spot+ cells were significantly correlated with SMA clinical classification and the copy numbers of the SMN2 gene. The range of values for cord blood, converted from each SMN2 copy number statistics, was − 0.7 to + 2.0 standard deviation (SD) (0.1–24.0%) for SMN-spot+ cells in patients with SMA. Subsequent analyses of the peripheral blood of neonates ranged from − 0.8 to + 0.8 SD (0.4–15.2%). The analysis of each maternal blood, converted from carrier statistics, ranged from − 0.2 to + 2.4 SD (1.4–25.2%). A correlation was observed between the cord blood and maternal peripheral blood. Conclusions This study suggests that the status of the motor neuron pool in the spinal cord can be presumed by cord blood SMN-spot+ cells and that SMN protein depletion determines the timing of disease onset. As the SMN spot analysis values tended to decrease with time after birth, they may eventually lead to the development of SMA. Furthermore, a correlation was found between the SMN spot analysis values of neonatal cord blood and maternal blood, which predicts disease severity after birth. In other words, the SMN protein supplied from the mother to the foetus may suppress the development of SMA in the infant at birth, and depletion of the SMN protein may occur after birth, causing the infant to develop SMA. Our findings demonstrated the effectiveness of newborn screening and the potential of maternally mediated treatment strategies by providing a rationale for prompt treatment initiation in SMA.